A Review Work on High Frequency Induction Curing of Porous Asphalt Concrete - Kaushik Neogi; Pradip Kumar Sadhu; Atanu Banerjee (Institute of Advanced Engineering and Science, 2016)
Induction heating method is a well known process to produce heat in a localized area on a susceptible metallic object. High frequency power, a work coil and an ancillary instrument part is the basis of induction heating. It is used in industrial and domestic areas where uniform and rapid heating is absolutely essential. As it is highly needed, in this research work, the effectiveness of induction heating will be verified by different curing methods. Firstly to initiate the asphalt concrete curing by high frequency induction heating so that the concrete become durable, electrically conductive and appropriately adjusted for induction heating, steel wire mesh / GI wire mesh is employed which is a good conductor of electricity. Now when micro cracks are likely to occur in asphalt product, the temperature of the asphalt material can be made high by induction heating of the steel wire mesh / GI wire mesh due to which the micro cracks are repaired itself and cracks are repaired by the increased temperature curing of bitumen by the physical process of diffusion and flow of the material. Consequent upon the repair, pre repair of small cracks, major cracks fail to occur protecting the road and thus ravelling of the road prevented to a great extent.